Pemasaran dalam Perspektif Ekonomi Islam - Hajar Swara Prihatta (Maliyah : Jurnal Hukum Bisnis Islam, 2018)
This article discusses marketing from an Islamic perspective. This article is the result of a literature review with data collection through books, journals, and articles. The collected data were analyzed qualitatively. In an economic system, marketing or marketing is an important thing to do to achieve product sales targets so that the business can be successful. To achieve business targets, several market players do not pay attention to marketing ethics. In Islam the Prophet has taught business ethics, including marketing through the nature of the Prophet which is abbreviated as SAFT (shiddiq, amanah, fathanah, and tabligh). Also, marketers must pay attention to theistic (rabbaniyyah), ethical (akhlaqiyyah), realistic (al-waqi’iyyah), and humanistic (insaniyyah) ethics. By paying attention to the marketing concept in Islam, it is hoped that there will be no marketing that can harm various parties, especially consumers and business partners.